The Jama Masjid Mohammedan Mosque; Queen Street, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Wilson and Johnstone, Trinidad, 2010)
Photograph of the Jama Masjid Mohammedan mosque located at the corner of the Piccadilly and Queen Streets in Port of Spain, Trinidad and Tobago. Postcard number J253.
Colour: Black and White Hues; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Church buildings--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Architecture--Trinidad and Tobago; Islam and architecture--Trinidad and Tobago